Pertanggungjawaban Pidana Pelaku Penipuan dengan Modus Kerja Sama usaha: Studi Putusan Nomor 75/Pid.B/2024/PN Kbu - Dea Novitasari (Jurnal Hukum Lex Generalis, 2026)
The crime of fraud under the guise of business cooperation is a form of crime that exploits the victim's trust through a series of systematic lies. This study aims to analyze the perpetrator's criminal liability based on Article 378 of the Criminal Code and the judge's considerations in Decision Number 75/Pid.B/2024/PN Kbu. The method used is normative juridical with a case approach. The results of the study indicate that the element of fault in the form of intent (dolus) is fulfilled and there is no justification or excuse and the judge emphasized the element of deception as the core of the crime. Therefore, it is recommended that law enforcement officers be more careful in distinguishing between fraud and breach of contract to ensure legal certainty.